Innovative Treatment of Organic Contaminants in Reverse Osmosis Concentrate from Water Reuse: a Mini Review - Xiang, Qun; Nomura, Youhei; Fukahori, Shuji; Mizuno, Tadao; Tanaka, Hiroaki; Fujiwara, Taku (Current pollution reports, 2019)
Reverse osmosis concentrate (ROC) from wastewater reclamation in water reuse retains concentrated toxic bio-refractory organics, and developing technologies for their removal is essential. This paper reviews innovative treatment technologies for organic contaminants in the ROC, and treatment options for applications are proposed. To adequately manage ROC, volume reduction and quality improvement are important. Forward osmosis (FO) can reduce the ROC volume. Advanced oxidation processes (AOPs) result in degrading organic contaminants and producing biodegradable organics, but the reduction of energy consumption is required. Coagulation is an effective option as a pre-treatment of AOPs and can improve the biodegradability of ROC. Partial use of short-time AOPs can transform high molecular weight organics into relatively biodegradable organics. Among AOPs, a rotating advanced oxidation contactor (RAOC) can be an energy-saving technique for removing bio-refractory organics from ROC using solar light irradiation. Post-biological treatment can significantly save energy and efficiently eliminate biodegradable organics that are produced by AOPs. Microalgae cultivation is also an effective option for resource recovery from ROC. Considering the techniques, an integrated process comprising FO, pre-coagulation, short-time and/or solar-driven AOPs (e.g., RAOC), and post-biological treatment is proposed as an energy-saving and cost-effective technology for ROC treatment.